2022
DOI: 10.1093/ehjci/jeab289.202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of coaptation gap in patients receiving tricuspid transcatheter edge-to-edge repair: initial observations from the bRIGHT TriClip study

Abstract: Funding Acknowledgements Type of funding sources: Private company. Main funding source(s): Abbott Background As tricuspid transcatheter edge-to-edge repair (TEER) gains momentum, the proper measurement of coaptation gap to determine optimal patients for this therapy becomes increasingly important. Currently, a single septo-lateral measurement from the short-axis transgastric (SAX TG) or RV inflow/outflow biplane view is commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The suitable anatomical structure of TV includes leaflet lengths exceeding 7 mm, a coaptation gap between 3 and 7 mm, and a central TR jet within the anteroseptal commissure [22,51]. Notably, 30-day follow-up data from the bRIGHT study have suggested that T-TEER achieves similar TR decreases among patients with coaptation gaps of <7 mm, 7-10 mm, and >10 mm [52]. Moreover, patients without cardiac implantable electronic devices are preferred for this procedure.…”
Section: Patient Selection For T-teermentioning
confidence: 99%
“…The suitable anatomical structure of TV includes leaflet lengths exceeding 7 mm, a coaptation gap between 3 and 7 mm, and a central TR jet within the anteroseptal commissure [22,51]. Notably, 30-day follow-up data from the bRIGHT study have suggested that T-TEER achieves similar TR decreases among patients with coaptation gaps of <7 mm, 7-10 mm, and >10 mm [52]. Moreover, patients without cardiac implantable electronic devices are preferred for this procedure.…”
Section: Patient Selection For T-teermentioning
confidence: 99%
“…Evaluation of tricuspid leaflet morphology is relevant in pre-procedural assessment as increasingly complex leaflet morphologies may be unfavorable for procedural efficacy of TEER ( 39 , 40 ). Importantly, coaptation gaps should only be measured from the transgastric 2D short-axis views if the leaflet tips are imaged; studies suggest that this view frequently overestimates these gaps compared to the RV inflow-outflow views ( 41 ). TV morphology and leaflet characterization may thus be more accurately assessed with 3D echocardiography and multi-planar reconstruction.…”
Section: Tricuspid Valve Multimodality Imagingmentioning
confidence: 99%